Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1001/jama.280.14.1238
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of Nurse Home Visitation on Children's Criminal and Antisocial Behavior

Abstract: Context.-A program of home visitation by nurses has been shown to affect the rates of maternal welfare dependence, criminality, problems due to use of substances, and child abuse and neglect. However, the long-term effects of this program on children's antisocial behavior have not been examined. Objective.-To examine the long-term effects of a program of prenatal and early childhood home visitation by nurses on children's antisocial behavior. Design.-Fifteen-year follow-up of a randomized trial. Interviews wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 981 publications
(269 citation statements)
references
References 33 publications
3
257
0
4
Order By: Relevance
“…Many county and state policy makers are beginning to realize this. They have chosen to increase or redirect social service funding to support effective, albeit expensive, prevention programs like the Nurse-Family Partnership (Olds et al, 1998; see also www.NCCFC.Org/nurseFamilyPartnership.cfm). Given the scant evidence of effectiveness for outpatient mental health services as they typically are delivered in the community (Weisz, Weiss, & Donenberg, 1992), there is clearly a need to be more strategic, meticulous, and innovative in our attempts to reduce the prevalence of conduct problems.…”
Section: Discussionmentioning
confidence: 99%
“…Many county and state policy makers are beginning to realize this. They have chosen to increase or redirect social service funding to support effective, albeit expensive, prevention programs like the Nurse-Family Partnership (Olds et al, 1998; see also www.NCCFC.Org/nurseFamilyPartnership.cfm). Given the scant evidence of effectiveness for outpatient mental health services as they typically are delivered in the community (Weisz, Weiss, & Donenberg, 1992), there is clearly a need to be more strategic, meticulous, and innovative in our attempts to reduce the prevalence of conduct problems.…”
Section: Discussionmentioning
confidence: 99%
“…These children were obviously also at high risk of CPA. The long-term follow-up of the children from the intervention group showed that they were less frequently abused and neglected, and also less likely to exhibit delinquent behaviours during adolescence (Olds et al 1986(Olds et al , 1998.…”
Section: Have Early Childhood Interventions Been Shown To Prevent Chrmentioning
confidence: 99%
“…For instance, a nurse visitation program for new mothers reduces antisocial behavior in their offspring even 15 years after the intervention. 35 This is an important contribution but there is no evidence that such public health interventions reduce morbidity and mortality of schizophrenia, mood disorders, or autism. Psychiatry will need to develop strategies for prevention for each of these disorders.…”
Section: Preventionmentioning
confidence: 99%